2012
DOI: 10.1515/hf.2011.185
|View full text |Cite
|
Sign up to set email alerts
|

New diarylpropanoids from Lindera glauca Bl. heartwood

Abstract: From the heartwood of Lindera glauca Blume three new diarylpropanoids have been isolated and identifi ed, which were named lindeglaucol, lindeglaucone, and lindeglaucoside A. Chipped heartwood was extracted repeatedly with 80 % aqueous methanol (MeOH) at room temperature, and the concentrated methanolic extract was successively partitioned with ethyl acetate (EtOAc), n -butanol, and H 2 O. From the EtOAc fraction, three new diarylpropanoids and a known chalconoid were isolated through repeated column chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The chemical structures of the isolated flavonoids were determined spectroscopically by means of IR, EI/MS, FAB/MS and NMR data as shown in Figure 1. Compounds 1 -8 were identified as lindeglaucol (1), lindeglaucone (2), cilicicone B (3), tamarixetin 3-O-a-Lrhamnoside (4), procyanidin A2 (5), cinnamtannin B1 (6), cinnamtannin D1 (7) and procyanidin A1 (8) with confirmation by comparing their spectroscopic data with those in the literature (Nonaka et al 1983;Kamiya et al 2001;Son et al 2005;Ahmed & Al-Howiriny 2007;Koerner et al 2009;Tomochika et al 2011;Huh et al 2012). …”
Section: Phytochemistrymentioning
confidence: 72%
See 3 more Smart Citations
“…The chemical structures of the isolated flavonoids were determined spectroscopically by means of IR, EI/MS, FAB/MS and NMR data as shown in Figure 1. Compounds 1 -8 were identified as lindeglaucol (1), lindeglaucone (2), cilicicone B (3), tamarixetin 3-O-a-Lrhamnoside (4), procyanidin A2 (5), cinnamtannin B1 (6), cinnamtannin D1 (7) and procyanidin A1 (8) with confirmation by comparing their spectroscopic data with those in the literature (Nonaka et al 1983;Kamiya et al 2001;Son et al 2005;Ahmed & Al-Howiriny 2007;Koerner et al 2009;Tomochika et al 2011;Huh et al 2012). …”
Section: Phytochemistrymentioning
confidence: 72%
“…Subsequently, extracts from other Lindera species such as Lindera umbellate and Lindera fruticosa have been reported to counteract LDL-oxidation, and procyanidin A2 is an inhibitor of LDL-oxidation (Katsube et al 2004;Song et al 2006;Hsieh et al 2008). Our own recent study of the heartwood of this plant revealed the chemical structure of four diarylpropanoids and three steroids (Huh et al 2011(Huh et al , 2012. In this study, five flavonoids were additionally isolated and identified from L. glauca heartwood.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The investigation of such naturally bioactive compounds isolated from tree residue is a permanent attraction and challenge, which still leads to new discoveries ( Huh et al 2012 ;Smeds et al 2012 ;da Silva et al 2013 ;Dedic et al 2014 ;In et al 2014 ;Latva-Maenpaa et al 2014 ;Vek et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%